2017
DOI: 10.1002/2016jd025967
|View full text |Cite
|
Sign up to set email alerts
|

South Asian summer monsoon breaks: Process‐based diagnostics in HIRHAM5

Abstract: This study assesses the ability of a high‐resolution downscaling simulation with the regional climate model (RCM) HIRHAM5 in capturing the monsoon basic state and boreal summer intraseasonal variability (BSISV) over South Asia with focus on moist and radiative processes during 1979–2012. A process‐based vertically integrated moist static energy (MSE) budget is performed to understand the model's fidelity in representing leading processes that govern the monsoon breaks over continental India. In the climatology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…Given that monsoon region is data sparse and model prejudices influence reanalysis thermodynamical variables, results from CFSR too need to be verified with sustained observations. Overall, our budget analysis, consistent with the earlier works (Prasanna and Annamalai, 2012;Hanf et al, 2017;Mohan and Annamalai, under review), provide robustness in precursor signals and false alarms in key ocean and atmospheric variables during the evolution of extended monsoon episodes.…”
Section: Individual Eventssupporting
confidence: 88%
“…Given that monsoon region is data sparse and model prejudices influence reanalysis thermodynamical variables, results from CFSR too need to be verified with sustained observations. Overall, our budget analysis, consistent with the earlier works (Prasanna and Annamalai, 2012;Hanf et al, 2017;Mohan and Annamalai, under review), provide robustness in precursor signals and false alarms in key ocean and atmospheric variables during the evolution of extended monsoon episodes.…”
Section: Individual Eventssupporting
confidence: 88%
“…A corresponding distribution pattern for RR10mm and RR20mm in the FF period under a high emission scenario (SSP5-8.5) is observed (Fig. 8b and c); however, there is a distinguished shift in curves to the right side and the curves become somehow flattened for RR20mm, showing an increase in the intensity of precipitation but a decrease in the frequency of precipitation, which may lead to the intensification of the water cycle in the future (Hanf et al, 2017). Under the SSP5-8.5 scenario, the RR50mm curves shift to the right in the FF period, and the simulated maximum precipitation value reaches up to 0.04 mm (Fig.…”
Section: Probability Distribution Of Precipitation Extremesmentioning
confidence: 77%
“…Therefore, a residual component arises in both reanalysis and modeled MSE budgets. However, based on earlier studies (e.g., Neelin and Su 2005;Maloney 2009;Annamalai et al 2014;Hanf et al 2017), the leading processes identified are expected to be robust and reproducible. To assess model biases, we point out errors in sources and sinks of column moisture or MSE.…”
Section: B Mse Budgetmentioning
confidence: 91%